1975
DOI: 10.1161/01.cir.51.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory and metabolic effects of glycerol infusion in patients with recent cerebral infarction.

Abstract: The effect of intravenous infusion of 10 per cent glycerol on regional cerebral blood flow (using hydrogen bolus and Xenon-133 (133Xe) clearance methods) and metabolism was investigated in 57 patients with recent cerebral infarction. Hemispheric blood flow (HBF) increased, together with increase in regional cerebral blood flow (rCBF) and cerebral blood volume (rCBV), in foci of brain ischemia. Hemispheric oxygen consumption (HMIO2) decreased together with hemispheric respiratory quotient. Systemic blood levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 37 publications
1
40
0
2
Order By: Relevance
“…34 It has been shown that glycerol improves the neurological status in patients with cerebral infarction by enhancing regional cerebral blood flow in the ischemic brain secondary to reduction of focal cerebral edema. 35,36 Recently, it has been shown that several compounds that can inhibit postischemic edema also reduce ischemic infarction. These compounds include NS-7, a novel N ϩ /Ca 2ϩ channel blocker 1 ; mannitol 37 ; S-0139, an endothelin type A receptor antagonist 9 ; MDL 72527, a polyamine oxidase inhibitor 8 ; and human albumin.…”
Section: Discussionmentioning
confidence: 99%
“…34 It has been shown that glycerol improves the neurological status in patients with cerebral infarction by enhancing regional cerebral blood flow in the ischemic brain secondary to reduction of focal cerebral edema. 35,36 Recently, it has been shown that several compounds that can inhibit postischemic edema also reduce ischemic infarction. These compounds include NS-7, a novel N ϩ /Ca 2ϩ channel blocker 1 ; mannitol 37 ; S-0139, an endothelin type A receptor antagonist 9 ; MDL 72527, a polyamine oxidase inhibitor 8 ; and human albumin.…”
Section: Discussionmentioning
confidence: 99%
“…28 Following temporary ischemia induced in baboons by occluding the carotid and vertebral arteries bilaterally, glycerol injection (1 g/kg) was found to be effective in reducing intracranial pressure and increasing cerebral blood flow. 29 In patients with cerebral infarction, numerous studies have evidenced the effectiveness of glycerol in reducing cerebral edema [30][31][32][33][34][35][36][37][38] and increasing cerebral blood flow. [36][37][38] Other studies 39 " 42 failed to observe any benefit from the use of glycerol, especially in patients with severe disability.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with recent cerebral infarction, glycerol infusion led to a decrease in cerebral oxygen consumption and carbon dioxide production whereas glucose consumption, pyruvate and lactate production by brain were found to be unchanged. 36 - 38 It was hypothesized that glycerol may cause a reversal of uncoupled oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In human stroke, increase of blood flow to ischemic territories and improvement in ischemic brain energy metabolism after glycerol administration have also been postulated. 35 The occurrence of a rebound phenomenon has been controversial, 12 but glycerol has the theoretical advantage over other osmotics in being metabolized by the brain on crossing BBB, thus reducing the risk of rebound edema. Using MRI before and after glycerol administration in 6 patients with large hemispheric infarction, no effect on tissue shift and noninfarcted hemisphere volume has been observed.…”
Section: Glycerolmentioning
confidence: 99%